Improving Writing Skills Using Artificial Intelligence (AI) on the ChatGPT Platform - Desmiyanti, Desmiyanti; Silvia, Resi (JELT: Journal of English Language Teaching, 2025)
The development of digital technology, especially AI-based natural language processing such as ChatGPT, has opened up new opportunities in the world of education, especially in improving academic literacy skills. This study aims to determine (1) How the use of the Artificial Intelligence (AI)-based ChatGPT platform can improve students' writing skills in learning English (2) The positive impacts and challenges faced by students in using ChatGPT as a writing learning medium. By using a qualitative method with a literature study approach, this study analyzed various scientific articles, books, journals, and previous research reports. The results of the study (1) Based on an in-depth literature study, it can be concluded that the use of the Artificial Intelligence (AI)-based ChatGPT platform can significantly improve students' writing skills in learning English. Through responsive, adaptive, and personalized interactions, ChatGPT provides support in various aspects of writing such as structure, vocabulary, grammar, and style. This platform functions as a virtual tutor, a source of inspiration, and a reflection tool that encourages students to be more confident and active in writing (2) Based on the analyzed literature study, the use of ChatGPT has a significant positive impact on the development of students' writing skills. Students receive assistance in improving their writing structure, expanding their vocabulary, and gaining writing inspiration.